China, Japan and regional leadership in East Asia - Dent, Christopher M. 1965- (Edward Elgar, 2008)
This book considers themes, evidence and ideas relating to the prospects for regional leadership in East Asia, with particular reference to China and Japan assuming regional leader actor roles. Key issues discussed by the list of distinguished contributors include: the extent to which there is an East Asian region to lead ChinaJapan relations different aspects of Japan and Chinas positions in the East Asia region how the seemingly inexorable rise of China is being addressed within theregion how China and Japan have explored paths of regional leadership throughcertain regional and multilateral organisations and frameworks the position of certain intermediary powers (i.e. the United States andKorea) with regards to regional leadership diplomacy in East Asia.Invaluably, the concluding chapter brings together the main findings of the book and presents new analytical approaches for studying the nature of, and prospects for leadership in East Asia.China, Japan and Regional Leadership in East Asia will be essential reading for upper level undergraduate and postgraduate students and researchers of international relations, regional studies, international political economy and economics as well as Asian and development studies.